2009
DOI: 10.1016/j.neuroimage.2008.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Long-term motor training induced changes in regional cerebral blood flow in both task and resting states

Abstract: Neuroimaging studies of functional activation often only reflect differentiated involvement of brain regions compared between task performance and control states. Signals common for both states are typically not revealed. Previous motor learning studies have shown that extensive motor skill training can induce profound changes in regional activity in both task and control states. To address the issue of brain activity changes in the resting-state, we explored long-term motor training induced neuronal and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
90
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 75 publications
11
90
3
Order By: Relevance
“…We argue that this finding may reflect different consequences of training phases between short-term training in Albert et al (2009) and longterm athletic training in the present study. This notion is consistent with Xiong et al (2009), who showed that regionspecific brain activation increases first, then decreases, during a longer period of motor training.…”
Section: The Role Of the Fronto-parietal Networksupporting
confidence: 91%
See 1 more Smart Citation
“…We argue that this finding may reflect different consequences of training phases between short-term training in Albert et al (2009) and longterm athletic training in the present study. This notion is consistent with Xiong et al (2009), who showed that regionspecific brain activation increases first, then decreases, during a longer period of motor training.…”
Section: The Role Of the Fronto-parietal Networksupporting
confidence: 91%
“…Since resting-state fc-fMRI does not involve any particular motor or cognitive task requirements, it may reflect a cumulative effect of experience over time (Lewis et al, 2009). Recent fc-fMRI studies have suggested that motor training altered resting-state brain activity (Xiong et al, 2009;Albert et al, 2009). For example, Albert et al (2009) examined resting-state functional brain changes during motor training using independent component analysis (ICA) and found that motor learning, but not motor performance, significantly modulated resting-state functional connectivity in the fronto-parietal and cerebellar networks.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous high-temporal resolution fMRI at 4.0 T recorded the sequence of neural information processing at the 100 msec time scale (42). In addition, differences in the power spectrum of resting state fMRI data before and after longterm motor training have recently been observed (43). Given the high-temporal resolution and real-time capability of the MECV sequence, it is of interest to explore whether these or other fMRI signal properties can be used as feedback metrics to modulate behavioral performance, as well as the relationship between fMRI NF signals and their electrophysiological counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…These brain networks do not require a task to exhibit synchrony and in humans include those brain areas associated with the motor system (Biswal et al, 1995;De Luca et al, 2005;Xiong et al, 2009), visual processing (Greicius et al, 2003), and auditory perception (Hunter et al, 2006). The major function of RSNs is thought to be to maintain dynamic connectivity among related functional networks so that these may process internal and external signals automatically and reliably (Buckner and Vincent, 2007;Greicius and Menon, 2004;Raichle et al, 2001).…”
Section: Introductionmentioning
confidence: 99%